IMPLEMENTATION OF DIGITAL LITERACY COMPETENCY AT SENIOR HIGH SCHOOL IN JAKARTA - Sinaga, Floren Agnesia; Dewanti, Ratna; Darmahusni (International Journal of Engineering Technologies and Management Research, 2021)
The development and implementation of information and technology in education, give an impact to literacy. The implementation of information and technology with literacy is known as digital literacy. Digital literacy not only talks about the skill or competency of using technology as a teacher in the learning process, but how school as a formal education institution can help the students to have digital literacy competency since this skill is needed by the students and teachers who are imposed by the technology as an impact of the pandemic. Schools not only have a responsibility to educate students about digital literacy competency in the learning process, but in all the school aspects must support the implementation of digital literacy. This research wants to explore how digital literacy competency has been implemented at senior high school level in Indonesia. Therefore, this descriptive qualitative research objective is to explore the digital literacy competency implemented at Citra Kasih School in Indonesia. The data collection techniques used in this research were observing and interviewing the principal by asking questions that had passed the validity test. Following the digital literacy competency which was set by Indonesian Ministry of Education and Culture (2017), this research explored the implementation of digital competency into three bases, class based, school environment based, and community based. From the research, it can be concluded that Citra Kasih Senior High School has applied three bases of digital literacy competency indicator at school. In the class based, Citra Kasih Senior High School has attended digital literacy training, applied and utilized digital literacy, and understood how to use digital media and the internet. Based on the school environment Sekolah Citra Kasih High School has implemented digital literacy in reading references, book borrowing frequencies, school activity, school policy. School service, and information presentation. However, on community based, Citra Kasih Senior High School has implemented digital literacy in facilities and infrastructure and in the involvement of parents and institutions.